Efficient synthesis of lower rim α-hydrazino tetrazolocalix[4]arenes via an Ugi-azide multicomponent reaction - Alavijeh, Nahid S.; Zadmard, Reza; Ramezanpour, Sorour; Balalaie, Saeed; Alavijeh, Mohammad S.; Rominger, Frank (New journal of chemistry, 2015)
In this study, we developed an efficient synthesis of α-hydrazino tetrazolocalix[4]arene derivatives in good yields under mild conditions via an Ugi-azide multicomponent reaction. Metal ion binding properties of one of the α-hydrazino tetrazolocalix[4]arenes (7a) as the model compound were also investigated, revealing that compound 7a exhibits the highest binding affinity towards Ni(II).